2006
DOI: 10.1007/s00464-005-0210-x
|View full text |Cite
|
Sign up to set email alerts
|

Is testicular perfusion influenced during laparoscopic inguınal hernia surgery?

Abstract: Testicular blood flow is influenced during laparoscopic inguinal hernia surgery. Whether changes in flow parameters remain in the late postoperative period, and whether they have an impact on complications will be evaluated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“…In contrast, we could not find significant differences in the testicular volume regardless of the technique and mesh used. Ersin et al [20] investigated postoperative changes of blood flow following Lichtenstein and TEP and found significantly altered flow parameters for each group compared with preoperative, very early postoperative, and early postoperative values.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, we could not find significant differences in the testicular volume regardless of the technique and mesh used. Ersin et al [20] investigated postoperative changes of blood flow following Lichtenstein and TEP and found significantly altered flow parameters for each group compared with preoperative, very early postoperative, and early postoperative values.…”
Section: Discussionmentioning
confidence: 97%
“…Pantaloon and indirect on one side each 1 structures such as vas [5], testicular vessels [18], and nerves [19] in this cicatrix has been debated earlier.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed, pain is also a marker of entrapment of structure in the MAST complex. Apart from purely sensory structures, entrapment of vas [4] and testicular vessels [18] is a possibility. Entrapment of vas leading to obstructive azoospermia, ejaculatory pain, and deterioration of sexual life has been reported earlier [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…It would have been very useful to observe for how long these flow alterations remained, considering that the subsequent examination was only done in the sixth month after the operation. Ersin et al 28 performed early examinations and observed alterations in the systolic and diastolic velocities only in the group that underwent the operation using the laparoscopic extraperitoneal (TEP) technique. The various studies discussed here lead to a common point: preservation of testicular function and fertility in men with inguinal hernias.…”
Section: Analysis Of the Testicular Flowmentioning
confidence: 99%